binomial theoram

Asked by gappus | 15th Feb, 2010, 07:28: PM

Expert Answer:

Do it systematically, for example,

(a+b)n = an + nan-1b + n(n-1)an-2b2/(1.2) + n(n-1)(n-2)an-3b3/(1.2.3) +.................+ bn 

Comparing (1-2x)5 we write, a = 1 and b = -2x.

(1-2x)5 = (1)5 - 5(1)5-1(2x)1 + 5x4(1)5-2(-2x)2/(1.2) + 5(5-1)(5-2)(1)5-3(-2x)3/(1.2.3) +

5(5-1)(5-2)(5-3)15-4(-2x)4/(1.2.3.4) + 5(5-1)(5-2)(5-3)(5-4)15-5(-2x)5/(1.2.3.4.5)

= 1 - 10x + 40x2 - 80x3 + 80x4 - 32x5

Regards,

Team,

TopperLearning

Answered by  | 16th Feb, 2010, 06:15: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.